BIOMATERIALS IN TRANSCATHETER AORTIC VALVE IMPLANTATION (TAVI): ENGINEERING INNOVATIONS AND THEIR IMPACT ON PATIENT QUALITY OF LIFE IN AN AGING SOCIETY - Mikołaj Zalewski,; Marianna Rudzińska,; Konrad Zieliński,; Jagoda Józefczyk,; Łukasz Krzystek,; Karolina Buć,; Paweł Buć,; Karolina Ganczar,; Stanisław Jurkowski,; Michał Mazurek, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Severe aortic stenosis (AS) constitutes a significant epidemiological challenge in aging populations, frequently referenced in the context of the "Silver Tsunami." Transcatheter aortic valve implantation (TAVI) has transitioned remarkably from a high-risk or prohibitive-risk intervention to a standard treatment strategy, thereby facilitating accelerated recovery and improved social functioning for elderly patients. The widespread clinical success of this method is inextricably linked to continuous advancements in material science and device engineering.Aim: This study conducts a comparative analysis of the leading material technologies utilized in transcatheter heart valve (THV) devices: specifically, Nitinol-based self-expanding valves (SEV) and cobalt-chromium (CoCr)-based balloon-expandable valves (BEV), alongside the performance of contemporary biological leaflet materials. The primary objective is to critically evaluate the influence of these material characteristics on long-term durability, valve hemodynamics, the incidence of prosthesis-patient mismatch (PPM), and the resulting impact on patient quality of life (QoL) and healthcare system resource utilization throughout the patient's lifetime management.Methods: A systematic synthesis of available literature and clinical trial data spanning the years 2018–2025 was performed, drawing primarily on outcomes from pivotal randomized clinical trials, notably PARTNER 3 (BEV) and EVOLUT Low Risk (SEV), complemented by specialized engineering reports on material fatigue and biocompatibility. The investigation focused on quantifying the correlation between the physicochemical properties of the implant—including stent alloy composition, leaflet configuration, and deployment behavior (e.g., ellipticity)—and critical clinical endpoints defined by the Valve Academic Research Consortium 3 (VARC-3). Emphasis was placed on complications impacting the patient’s socio-functional outcomes, such as structural valve deterioration (SVD), severe PPM, and the complexity of coronary re-access during prospective redo procedures.Findings: Comparative data consistently indicate that SEV platforms, leveraging the properties of Nitinol, are associated with superior post-procedural hemodynamics, including lower mean gradients and larger effective orifice area (EOA), relative both to surgical valves and often to BEV, particularly within the challenging anatomical context of a small aortic annulus. Specifically, the utilization of SEV demonstrated a lower rate of severe PPM (9.0%) compared to BEV (24.0%) in patients with extra-small aortic annuli. Furthermore, long-term follow-up (up to 10 years) confirms that TAVI with early-generation SEV provides durable hemodynamic performance and low rates of SVD and bioprosthetic valve failure (BVF). These analytical results underscore the necessity of optimizing material selection, focusing on devices capable of delivering superior hemodynamic profiles to ensure prolonged prosthetic efficacy and minimize the resource-intensive burden associated with subsequent re-interventions in a population enjoying increasingly extended life expectancy.Conclusions: The decision matrix concerning biomaterial selection within transcatheter aortic valve implantation (TAVI) transcends conventional technical specifications, yielding profound socio-economic and long-term strategic implications in the management of severe aortic stenosis (AS). As the indications for TAVI broaden to encompass younger, lower-surgical-risk cohorts, maintaining the functional independence of this aging demographic ("Active Aging" strategy) relies critically on ensuring prosthetic valve durability and facilitating future re-interventions.Comparative analyses between self-expanding valves (SEV), typically constructed with Nitinol frames, and balloon-expandable valves (BEV), often incorporating cobalt-chromium or rhenium alloys, underscore material-dependent clinical heterogeneity. Data demonstrate that the inherent properties of SEV contribute to a more favorable post-procedural hemodynamic profile. Specifically, SEV deployment is associated with a markedly lower incidence of severe prosthesis-patient mismatch (PPM) (9.0% for SEV versus 24.0% for BEV in patients with extra-small aortic annuli), a crucial factor mitigating long-term mortality risk. Furthermore, extended follow-up (up to 10 years) confirms that SEV platforms exhibit durable hemodynamic performance and lower rates of structural valve deterioration (SVD) compared to surgical aortic valve replacement (SAVR), although rates of bioprosthetic valve failure (BVF) are comparably low.The future trajectory of material engineering in this domain is focused on reducing system profiles (e.g., Optimum TAV with the lowest SEV frame), mitigating long-term risks such as thrombogenicity, and simplifying subsequent "valve-in-valve" (TAV-in-TAV) procedures. The emergence of advanced polymeric heart valves (PHV), such as Foldax TRIA (utilizing LifePolymer), offers the prospect of durability exceeding 35 years in fatigue testing and elimination of the need for lifelong anticoagulation, which constitutes a fundamental change for patient quality of life (QoL) and reduction of the healthcare system burden (Health Technology Assessment). In the context of lifetime management planning, engineering tools such as computed tomography (CT) simulations become essential for personalizing device selection and predicting the feasibility of future TAV-in-TAV interventions, which is key for younger populations.